Glued multylayer slab spans in the deck structure of timber bridges - V. A. Utkin; G. M. Kadisov (Вестник СибАДИ, 2017)
The article studies the stress-strain state of multilayer laminated timber deck of cross planks, which are a supporting element in slab glulam bridge superstructures. Timber slab from an odd number of cross-layer boards can be considered homogeneous thin plate with different properties in different directions; on the other hand it represents the multilayered structure of welded (glued) homogeneous anisotropic layers.The work assesses the stress-strain state of multilayer timber slabs in relation to slab span structures of bridges.